Managers at work - Coates, Joseph F. (Research management (Now: research technology management))
Joseph F. Coates explains How to Recognize a Sound Technology Forecast. Followed by John Broadhead on Planning a Successful R&D Alliance, an an IRI survey of the 'Biggest' Problems Technology Leaders Face.